Varietal screening of Gerbera jamesonii for resistance to Alternaria blight - and SANJAY GOSWAMI, DIPAK T. NAGRALE*, ANIL P. GAIKWAD (Indian Phytopathology, 2013)
Twenty one varieties of Gerbera jamesonii were screened in polyhouse against Alternaria alternate by two methods of inoculation viz., ‘Micro-droplet inoculation techniques’ (MDIT) and ‘Mycelial bit inoculation method (MBIM). None of the variety was found completely free from disease. However, the blight disease reaction on gerbera plant in respect of disease intensity varied considerably in this study indicated that the only variety, ‘Tiramissu’ was resistant to Alternaria blight.